More than an apartheid loss : recovering and remembering Fairview, a 'lost' Group Areas history - Salo, Inge (Department of Environmental and Geographical Science, 2015)
Against the background of the Group Areas Act (1950) and the consequent forced removals this thesis recovers the history of Fairview, Port Elizabeth. I examine how this neighbourhood is remembered through oral histories, family photographs and memory maps, alongside archival, media and literary representations of the area at the time. I demonstrate that despite the forced removals of its residents and the physical destruction of a neighbourhood, Fairview continues to be actively re-imagined, in the present, in varied unpredictable ways. I draw upon earlier research about Apartheid forced removals and how the places affected are remembered by people who lived the trauma of forced eviction on racial grounds. I also draw upon my own qualitative research conducted in 2012 and 2013 to explore, the representation of place in both personal memories and archival material. Through this mix I present Fairview’s history of dispossession as a result of the Group Areas Act, and highlight the violence exercised through Apartheid-era legislation. However, I also present rich family and community histories comprised of meaningful relationships that were nurtured around enduring institutions which provide insight into the ‘everyday’ makings of a neighbourhood and its residents. By allowing these interconnected narratives to shape the memory of Fairview I demonstrate that recovering this history is about more than remembering an Apartheid loss. This work contributes to a broader project of refiguring and expanding the archive in post-Apartheid South Africa, a body of materials, that recognise its character as being plagued by colonial and later Apartheid biases (Hamilton, Harris and Reid, 2002: 9). I focus on broadening memories of places in which Apartheidera Group Areas removals and its destruction were imposed. To explore the multiple dimensions of these types of spaces I understand them as embodied social contexts which provide structure to inhabitants through multiple layers of community (Till, 2012: 9, 10, 2008: 108). This approach assists me to explore responses to acts of trauma like forced removals and demolitions, highlighting the various place-making activities through which people attempt to reconnect with their former neighbourhoods and lives, expressed in recollections, images and rituals which are central to how places of memory are remembered and reimagined (Till, 2003: 297). In the context of Fairview the mix of public and state archives with family repositories was central to recuperating and recovering a fuller history of Group Areas Removals and highlighting its meaningfulness in the present.